(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two Tortricid moths, Eana joannisi (Schawerda, 1929) and Eucosma balatonana (Osthelder, 1937), are reported for first time in the Italian fauna. E. joannisi was found on Gennargentu Mountains in Sardinia, E. balatonana was collected on Monte Campo in Molise region.